Effect of Diagnosis, Complications, and Nutrition for Using Nasogastric Tube to Body Weight of Child Patients with Feeding Difficulty at Dr. M. Djamil General Hospital, Padang, Indonesia - Youri, Riana; Gustina Lubis; Finny Fitry Yani; Aumas Pabuti; Didik Hariyanto; Yusri Dianne Jurnalis; Rinang Mariko (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Several conditions in children can cause nutritional intake via the oral route to be inadequate. Providing enteral nutrition via a nasogastric tube (NGT) is an alternative option. Research on the use of NGTs in Indonesia is still limited, so this research aims to determine the effect of NGT use on the weight of pediatric patients with feeding difficulties at Dr. M. Djamil General Hospital, Padang. Methods: Experimental research with a pre and post-test-only design was conducted on 96 children aged 1 month - 18 years in the children's inpatient room at Dr. M. Djamil General Hospital, Padang. Body weight measurements were carried out before and after using NGT for 4 weeks (January 2022 – January 2023) at the pediatric nutrition and metabolic diseases polyclinic. Data were analyzed using paired t-test and ANOVA. Results: Most subjects (40.9%) were in the 1-12 month age group. The most common type of nutrition was ONS (oral nutritional supplements) (84.4%), the most common diagnosis was pulmonology (33.3%), and the majority were without complications (72.9%). There is an influence on the child's weight before and after using NGT (p-value <0.01). Significant differences were also found in changes in children's weight with diagnosis and complications (p<0.01). Conclusion: The use of NGT can increase the weight of pediatric patients who have feeding difficulties at Dr. M. Djamil General Hospital, Padang. Significant differences were found in changes in children's weight by diagnosis and complications.